MODELISASI GRINDER KOPI MANUAL DENGAN PENGGABUNGAN KURVA BEZIER, KURVA HERMIT, DAN HASIL DEFORMASI TABUNG - Mohamad Febri Setiawan; Bagus Juliyanto; Firdaus Ubaidillah (UNEJ e-Proceeding, 2022)
A coffee grinder is a tool for grinding coffee beans into coffee grounds. A manual coffee grinder consists of three parts, namely the container, the body, and the swivel. In this study, a manual coffee grinder was modeled by combining Bezier curves, Hermit curves and tube deformation results. Manual coffee grinder modeling processes are divided into four stages. The first, modeling the manual coffee grinder by dividing into two models, namely model A and model B. The second, determining the size of the manual coffee grinder components based on the model. The third, modeling manual coffee grinder components. Finally, combine the ingredients to produce a complete and varied manual coffee grinder. The result of this study is a manual coffee grinder component procedure that varies with the deformation technique. The deformation techniques used are dilation and translation. Keywords: Bezier curve, Hermit curve, dilation, translation.